Base–Metal‐Catalyzed Regiodivergent Alkene Hydrosilylations. Issue 23 (25th April 2016) - Du, Xiaoyong; Zhang, Yanlu; Peng, Dongjie; Huang, Zheng
Abstract: A complementary set of base metal catalysts has been developed for regiodivergent alkene hydrosilylations: iron complexes of phosphine‐iminopyridine are selective for anti ‐Markovnikov hydrosilylations (linear/branched up to >99:1), while the cobalt complexes bearing the same type of ligands provide an unprecedented high level of Markovnikov selectivity (branched/linear up to >99:1). Both systems exhibit high efficiency and wide functional group tolerance. Abstract : Regiodivergent alkene hydrosilylation has been accomplished with high efficiency using a newly developed set of complementary base metal catalyst systems. An inversion of regioselectivity (linear/branched) from >99:1 to <1:99 is obtained when the iron version of the catalyst is exchanged for a cobalt‐containing analogue.